Barriers and avenues to labour market integration of Nepalese immigrants with international degree qualifications from Finnish higher education institutions in Finland - Kandangwa, Saroj (2022)
The research explores the obstacles confronted by the Nepalese immigrants with international degree qualifications from Finnish higher education institutions into the Finnish labour market and ways to overcome the obstacles or to facilitate their integration into the Finnish labour market. The research findings can be useful for the policy makers and concerned authorities to formulate policies and measures to facilitate integration of international degree students and graduates from the Nepalese nationality background into the Finnish labour market. They may also be useful for the community of international students and graduates from immigrant backgrounds looking to get integrated into the Finnish labour market.